Know it now: the effects of brief mental health workshop on secondary school students - Tan, Sin Yee; Phang, Jin Xiang (2019)
The prevalence of mental health issues among the secondary school students is increasing. Past studies illustrated that one in five adolescents is living with mental health issue. There are numerous findings highlighted the urgent need of delivery mental health related information to this target group to cultivate prevention or encouragement of early intervention. This research aimed to examine the effectiveness of brief mental health workshop on mental health literacy in the areas of mental health knowledge, mental illness stigma, and health seeking behaviour from mental health professionals among the secondary school students in Malaysia. This research was conducted by using quasi-experimental pretest posttest design on a brief mental health workshop among 94 students from an independence high school aged 16 to 19. Our findings indicated a significant increase in mental health knowledge (p < .001) and a significant decrease in mental illness stigma (p < .001), however, no significant difference was shown for help-seeking behaviour between the pretest and posttest. Males (M = 8.41, SD = 2.91) and females (M = 6.78, SD = 2.76) differ significantly in the pretest for mental illness stigma, t(92) = 2.75, p < .01. This study showed that a brief mental health workshop is viable to improve mental health knowledge and reduce mental illness stigma. This study provides evidence that a brief mental health workshop can elicit positive impacts in mental health literacy on Malaysian adolescents which born in a multiracial and multicultural context.